Replication Region Analysis Reveals Non-lambdoid Shiga Toxin Converting Bacteriophages - Llarena, Ann-Katrin; Aspholm, Marina; O’Sullivan, Kristin; Wêgrzyn, Grzegorz; Lindbäck, Toril (Frontiers in Microbiology, 2021)
Shiga toxin is the major virulence factor of enterohemorrhagic Escherichia coli (EHEC), and the gene encoding it is carried within the genome of Shiga toxin-converting phages (Stx-phages). Numerous Stx-phages have been sequenced to gain a better understanding of their contribution to the virulence potential of EHEC. The Stx-phages are classified into the lambdoid phage family based on similarities in lifestyle, gene arrangement, and nucleotide sequence to the lambda phages. This study explores the replication regions of non-lambdoid Shiga toxin-converting phages that completely lack the genes encoding the proteins involved in initiating replication in the lambdoid phage genome. Instead, they carry sequences encoding replication proteins that have not been described earlier, here referred to as eru genes (after EHEC phage replication unit genes). This study identified three different types of Eru-phages, where the Eru1-type is carried by the highly pathogenic EHEC strains that caused the Norwegian O103:H25 outbreak in 2006 and the O104:H4 strain that caused the large outbreak in Europe in 2011. We show that Eru1-phages exhibit a less stable lysogenic state than the classical lambdoid Stx-converting phages. As production of phage particles is accompanied by production of Stx toxin, the Eru1-phage could be associated with a high-virulence phenotype of the host EHEC strain. This finding emphasizes the importance of classifying Stx-converting phages according to their replication regions in addition to their Stx-type and could be used to develop a novel strategy to identify highly virulent EHEC strains for improved risk assessment and management.